1998
DOI: 10.1006/jmbi.1998.1943
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of local structure in proteins using a library of sequence-structure motifs

Abstract: We describe a new method for local protein structure prediction based on a library of short sequence pattern that correlate strongly with protein three-dimensional structural elements. The library was generated using an automated method for ®nding correlations between protein sequence and local structure, and contains most previously described local sequence-structure correlations as well as new relationships, including a diverging type-II b-turn, a frayed helix, and a proline-terminated helix. The query seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
268
2
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 310 publications
(276 citation statements)
references
References 47 publications
5
268
2
1
Order By: Relevance
“…SVM-pairwise uses the pairwise Smith-Waterman sequence similarity algorithm in place of the gradient vector in the SVM-Fisher method that we described earlier. In contrast, SVM-I-sites encodes the local structure composition of a protein as the sum of I-sites motif confidence scores, 16,17 where each motif defines one feature. After the vectorization step, all of the SVM-based methods will define a similarity score for 2 proteins based on the feature vectors and use that similarity as the kernel of the classifier.…”
Section: Results and Discussion Setup Of Competing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SVM-pairwise uses the pairwise Smith-Waterman sequence similarity algorithm in place of the gradient vector in the SVM-Fisher method that we described earlier. In contrast, SVM-I-sites encodes the local structure composition of a protein as the sum of I-sites motif confidence scores, 16,17 where each motif defines one feature. After the vectorization step, all of the SVM-based methods will define a similarity score for 2 proteins based on the feature vectors and use that similarity as the kernel of the classifier.…”
Section: Results and Discussion Setup Of Competing Methodsmentioning
confidence: 99%
“…Local structure motifs were found using the I-sites library of sequence-structure correlations. 17 The I-sites library contains 262 short-sequence patterns that each has a strong correlation with the three-dimensional (3D) structure, locally. Our tests showed that SVM-I-sites was comparable in detection accuracy and more efficient than the state-of-the-art method SVM-pairwise.…”
Section: Introductionmentioning
confidence: 99%
“…ArchDB is a compilation of structural classifications of loops extracted from known protein structures [15]. I-sites library contains a set of sequence patterns that strongly correlate with protein structure at the local level [16]. LSBSP1 and LSBSP2 contain large sets of sequence profiles for short segments, and these databases have been implemented in the integrated computational system PrISM.1 for predicting local structures [17,18].…”
Section: Featuresmentioning
confidence: 99%
“…To bridge the current protein structure-function research gap and address anterior questions, many approaches have been proposed for encoding 3D local structural fragments based on Cartesian coordinates into a one-dimensional representation using several letters called the structural alphabet [6]- [13]. The structural alphabet represents advantageous local structures and has been used to 1) compare/analyze 3D structures [14]- [16], 2) predict protein 3D structures from amino acid sequences [6], [9], 3) reconstruct protein backbones [11], and 4) model loops [17].…”
Section: Introductionmentioning
confidence: 99%
“…The structural alphabet represents advantageous local structures and has been used to 1) compare/analyze 3D structures [14]- [16], 2) predict protein 3D structures from amino acid sequences [6], [9], 3) reconstruct protein backbones [11], and 4) model loops [17]. In addition, given that local structures are generally more evolutionary conserved than amino acid sequences, a series of research has been developed to explore protein structures [18].…”
Section: Introductionmentioning
confidence: 99%